Critical Response to Article “Integrated Network Pharmacology and Experimental Validation Approach to Investigate the Mechanisms of Stigmasterol in the Treatment of Rheumatoid Arthritis” [Letter] - Rinendyaputri R; Panjaitan NSD (Dove Medical Press, 2023)
Ratih Rinendyaputri, Novaria Sari Dewi Panjaitan Center for Biomedical Research, Research Organization for Health, National Research and Innovation Agency (BRIN), Cibinong Science Center, Cibinong - Bogor, West Java, Km. 46, IndonesiaCorrespondence: Novaria Sari Dewi Panjaitan, Center for Biomedical Research, Research Organization for Health, National Research and Innovation Agency (BRIN), Cibinong Science Center, Jl. Raya Bogor No. 490, Cibinong – Bogor, West Java, Km. 46, Indonesia, Email nova014@brin.go.id